The Political Economy of a Diverse Monetary Union - Enrico Perotti; Oscar Soons (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2020)
We analyze the political economy of monetary unification among countries with different quality of institutions. Countries with stronger institutions have lower public spending and better investment incentives, even under a stronger currency. Governments under weaker institutions spend more so must occasionally devalue. In a MU market prices and ows adjust quickly but institutional differences persist, so a diverse monetary union (DMU) has redistributive effects. The government in the weaker country expands spending, and investment may be reduced by the fiscal and common exchange rate effect. Strong country production benefits from the weaker currency but needs to offer fiscal support in a crisis. In equilibrium the required support is incentive compatible due to the devaluation gain. Some governments may join a DMU even if it depresses productive capacity to expand public spending. Even in a DMU beneficial for all countries, firms in weaker countries and savers in stronger countries may lose.
Keywords: O33; O47; D72; F33; F45; 330; Monetary unions; institutional quality; fiscal union; political economy; fiscaltransfers